Prebiotics and Probiotics: Effects on Dyslipidemia and NAFLD/NASH and the Associated Mechanisms of Action - Rodríguez-Pastén, Alicia; Fernández-Martínez, Eduardo; Pérez-Hernández, Nury; Soria-Jasso, Luis E.; Cario-Cortés, Raquel (Current Pharmaceutical Biotechnology, 2023)
Background: Non-alcoholic fatty liver disease (NAFLD) is now considered the most common chronic liver disease worldwide. NAFLD is related to changes in lipid metabolism and is characterized by the increase or accumulation of fat in hepatocytes that may progress to nonalcoholic steatohepatitis (NASH), which leads to the appearance of inflammatory processes. Treatment consists of changes in diet, physical activity, and weight control; however, these disorders represent a health problem and require the development of novel alternatives to treatment and prevention. NAFLD/NASH are strongly associated with other disorders, such as metabolic syndrome (MetS); in fact, NAFLD is considered the hepatic manifestation of MetS. These disorders are related to other components of MetS, including dyslipidemia, which is characterized by an imbalance in blood cholesterol and triglyceride levels. Prebiotics and probiotics benefit from treating and preventing several ailments, including liver diseases. Specifically, in dyslipidemia, NAFLD, and NASH, probiotics play a fundamental role in conducting the biotransformation of primary bile acids into secondary bile acids, which generally have important activity as immunomodulators and metabolism regulators. The mechanisms of action of pre and probiotics involve the activity of bile acid receptors, such as FXR and TGR-5, and the events resulting from their activation. Therefore, prebiotics and probiotics may be reasonable options to prevent and treat metabolic- related liver diseases.
Keywords: TGR-5